Comparative Evaluation of C-Arm Guided and Open Intramedullary Pin Fixation for Long Bone Fractures in Dogs - G. G. Karad; S. D. Chepte; M.F.M.F. Siddiqui; N. M. Karad; S. Sajid Ali; S.D. More; G. M. Bontalwad; S. N. Nakade; A. R. Ghuge; V. D. Ambhore (Archives of Current Research International, 2025)
The present study was carried out on 12 clinical cases of dogs having long bone fractures. The dogs were randomly divided into two groups based on the methods used for fracture stabilization. The fractures were stabilized using intramedullary pinning either by the open reduction (group A, n=6) or the C-arm guided closed reduction method (group B, n=6). A higher incidence of fractures was observed in male dogs (66.67%) among which femur was most common (58.34 %) followed by tibia/fibula 25 %. The main causes of the fractures were automobile accidents (58.34%) followed by free falls from height (25%). Breed wise distribution found the highest incidence in non-descript dogs (50%) followed by German shepherds (25%). The dogs in the age group of 0-6 months were found most affected (41.67%), followed by the age group of 7-12 months (33.34%). The mean incision length and duration of surgery were shorter in group B as compared to group A. The mean radiographic healing score was higher in group-B than in group-A, although statistically non-significant. The lameness score decreased faster in group B compared to group A. C-arm guided intramedullary pinning is more suitable for transverse fracture as compared to oblique and comminuted fracture. The shorter incision lengths and operating times result in more rapid fracture healing and favour early ambulation with fewer post-operative complications.